Quantifying spatio-temporal patterns of urban expansion in Beijing during 1985–2013 with rural-urban development transformation. (May 2018) - Yang, Yuanyuan; Liu, Yansui; Li, Yurui; Du, Guoming
Highlights: Studying the landscape configuration, holistic change of urban land in area, size, expansion speed and movement direction. GIS-based buffer analysis was also applied to research spatial mode of urban expansion in Beijing. Beijing has undergone magnificent urban sprawl during 1985–2013. Urban sprawl presented denotative feature along the motorways while urban also expanded in the form of a big pancake. Abstract: Rural-urban development transformation has entered a crucial period with the development of urbanization, informatization, industrialization and agricultural modernization. Quantifying spatio-temporal patterns of urban expansion is essential to monitor and assess the process of urbanization and offer a theoretical basis for rural restructuring and landscape dynamics. In this paper, we used the remotely sensed land use data to quantify and research spatio-temporal patterns of urban expansion from 1985 to 2013 in Beijing, China. This study integrated methods of statistical analysis (i.e., calculation of time series landscape matrices and urban expansion index) and the gravity-center model to study the landscape configuration, the holistic change of urban land in area, size, expansion speed and movement direction, respectively. Meanwhile, GIS-based buffer analysis was also applied to study the spatial mode of urban expansion in Beijing. Results demonstrated that (1) Beijing has experienced magnificent urban sprawl in the last 28 years. The combination of time series landscape matrices exhibited a typical spatial configuration of urban sprawling in Beijing: leapfrog development of new urban nuclei formation in areas which were non-adjacent to existing urban centers with obvious fragmentation, as well as expansion of existing urban areas resulting in contiguous urban entities in each time interval; (2) The gravity center of urban land continued moving northeastward, except during the time intervals of 1995–2000 and 2010–2013 when it moved southward; (3) The northern fan-shaped suburb was the most active area of urban expansion before 2005, and urban later had a concentrated expansion toward the southern inverted-triangle-shaped area; and (4) Urban sprawl presented denotative features along the motorways, while urban also expanded in the form of a big pancake.